1992
DOI: 10.1007/bf00023391
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of an embryo-specific mRNA up-regulated in hydrated dormant seeds

Abstract: Dormant seeds do not germinate when imbibed in water even when conditions are favorable for germination. These hydrated seeds remain viable, but growth-arrested for weeks due to unknown restrictions within the embryo. As a model system for the study of the molecular processes occurring in dormant seeds, we have chosen to examine gene expression in Bromus secalinas, a grass species that produces seeds with high levels of embryonic dormancy. Using differential screening for mRNAs present in hydrated dormant embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 18 publications
2
53
0
1
Order By: Relevance
“…The largest ORF of the full-length B15C sequence ( Figure 2b) encodes a protein of 218 amino acids, which is identical to the protein encoded by the pBS128 cDNA from the grass species Bromus secalinus except for five amino acid substitutions (Goldmark et a/., 1992) (Figure 3b). In B. secalinus, this transcript is upregulated in dormant embryos after imbibition (Goldmark etal., 1992).…”
Section: The B15c Cdna Is Homologous To a Dormancy-related Transcriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest ORF of the full-length B15C sequence ( Figure 2b) encodes a protein of 218 amino acids, which is identical to the protein encoded by the pBS128 cDNA from the grass species Bromus secalinus except for five amino acid substitutions (Goldmark et a/., 1992) (Figure 3b). In B. secalinus, this transcript is upregulated in dormant embryos after imbibition (Goldmark etal., 1992).…”
Section: The B15c Cdna Is Homologous To a Dormancy-related Transcriptmentioning
confidence: 99%
“…The pBS128 transcript from B. secalinus, which is maintained at a high level in dormant, but not in nondormant hydrated seeds, has been suggested to play a role in the maintenance of embryo dormancy (Goldmark et a/., 1992). The presence of this transcript in embryos of downy brome (B. tectorum), common rye (Secale cereale), wild oat (Avena fatua), jointed goatgrass (Aegilops cylirtdrica) (Goldmark et a/., 1992) and perennial ryegrass ( Figure 6, lane 10) also suggests an important function in monocot seeds.…”
Section: B15c May Coordinate Dormancy In the Aleurone Layer And In Thmentioning
confidence: 99%
“…In contrast to GmPer1a, expression of the GmPer1b gene was barely detectable in soybean plants or seeds, suggesting again that GmPer1b is a pseudogene. It has been reported that 1-Cys Prx genes of various plants, including Per1 of barley (Aalen et al 1994), pBS128 of brome grass (Goldmark et al 1992), FePer1 of buckwheat (Lewis et al 2000), R1C-Prx of rice (Lee et al 2000) and AtPer1 of Arabidopsis (Haslekås et al (A) SDS-PAGE of synthesized and purified recombinant GmPer1a. His-tagged GmPer1a was synthesized by a wheat germ expression system and then applied to a Ni-Sepharose column.…”
mentioning
confidence: 99%
“…The plant 1-Cys Prx genes pBS128 from brome grass (Goldmark et al, 1992), Per1 in barley (also called B15C; Aalen et al, 1994), AtPER1 in Arabidopsis (Haslekås et al, 1998), and FePer1 from buckwheat (Fagopyrum esculentum; Lewis et al, 2000) are expressed in developing seeds. They have high expression levels during the stages of massive water loss at the end of seed development and also in the mature dry seed.…”
mentioning
confidence: 99%